2001
DOI: 10.1109/83.908504
|View full text |Cite
|
Sign up to set email alerts
|

Integer wavelet transform for embedded lossy to lossless image compression

Abstract: The use of the discrete wavelet transform (DWT) for embedded lossy image compression is now well established. One of the possible implementations of the DWT is the lifting scheme (LS). Because perfect reconstruction is granted by the structure of the LS, nonlinear transforms can be used, allowing efficient lossless compression as well. The integer wavelet transform (IWT) is one of them. This is an interesting alternative to the DWT because its rate-distortion performance is similar and the differences can be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 109 publications
(40 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…This can have an important impact on the computational cost when large amounts of data (as volumes) must be handled. Finally, it asymptotically reduces the computational complexity by a factor four [33], [34]. Due to the rounding operations, the integer coefficients are different from the corresponding true wavelet coefficients.…”
Section: Three-dimensional Integer Dwt Via Liftingmentioning
confidence: 99%
“…This can have an important impact on the computational cost when large amounts of data (as volumes) must be handled. Finally, it asymptotically reduces the computational complexity by a factor four [33], [34]. Due to the rounding operations, the integer coefficients are different from the corresponding true wavelet coefficients.…”
Section: Three-dimensional Integer Dwt Via Liftingmentioning
confidence: 99%
“…The observed oscillatory trend of the PSNR along the coordinate axis entails the analysis of both the rounding noise implied by integer lifting [18] and the quantization noise. Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Third, it is computationally efficient. It can be shown that the lifting steps implementation asymptotically reduces the computational complexity by a factor 4 with respect to the classical filter-bank implementation [18]. Finally, the transformation can be implemented in-place, namely progressively updating the values of the original samples, without allocating auxiliary memory.…”
Section: The 3-d/2-d Multidimensional Layered Zero Coding (Mlzc) mentioning
confidence: 99%
“…The SPIHT algorithm is affected by the characteristic oscillation of the PSNR with the slice index due to the rounding noise introduced by integer lifting. 7,8 Conversely JPEG2000 does not suffer from such shortcoming due to the post-compression rate distortion policy.…”
Section: Codingmentioning
confidence: 99%